2017
DOI: 10.1515/ijamh-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

The diurnal pattern of salivary IL-1β in healthy young adults

Abstract: Disruption in circadian rhythm affects the production of inflammatory cytokines. Understanding how it behaves in diseased conditions is essential. Despite the role of the interleukin-1β (IL-1β), a potent inflammatory cytokine, in human diseases, little is known about the steady-state circadian rhythm of IL-1β in healthy individuals. This short study investigates the diurnal pattern of salivary IL-1β throughout the day in healthy young adults. Twelve participants provided saliva samples at various times through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Their study reported that the salivary levels of most of the cytokines were highest in the morning. Similarly, other studies have also reported highest levels of IL‐1β 46 and IL‐6 47 in the morning. Although we did not assess the diurnal rhythm of the cytokines in the present study, all the samples were collected around 10:00 am to reduce the influence of diurnal variation.…”
Section: Discussionsupporting
confidence: 63%
“…Their study reported that the salivary levels of most of the cytokines were highest in the morning. Similarly, other studies have also reported highest levels of IL‐1β 46 and IL‐6 47 in the morning. Although we did not assess the diurnal rhythm of the cytokines in the present study, all the samples were collected around 10:00 am to reduce the influence of diurnal variation.…”
Section: Discussionsupporting
confidence: 63%
“…Cytokine levels can also be influenced by technical complications. For example, cytokines such as IL-1 and IL-6 exhibit diurnal variations, which can contribute to differing results among studies ( 34 , 35 ). The type of trauma can also impact on cytokine measurements.…”
Section: Immune Imbalances In Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…It should be noted that our study discussed time of saliva collection while others did not. However, diurnal patterns of cytokines may play a role in differences of cytokine levels (Ghazali et al, 2017). In addition, the heterogeneity of inflammation varies in relation to medications, age, and MS disease state (Beurel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even though we adhered to careful and standardized methods for saliva collection of cytokines, additional studies are needed in a larger sample to control for confounders (e.g., prior studies used blood measured cytokines; Milrad et al, 2018;Sorenson et al, 2013;Schmidt et al, 2016;Tsuboi et al, 2018;Wiener et al, 2019). However, we expect that the impact of these confounders is small because several authors have measured cytokines with saliva (Ghazali et al, 2017;Hanken et al, 2018;Szabo et al, 2016;Williamson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation